Pinnotherotonia rumphiusi gen. et sp. nov., a new furry bivalve-associated pontoniine shrimp (Crustacea: Decapoda: Palaemonidae) from Palau - Marin, Ivan; Paulay, Gustav (Zootaxa, 2010)
A new genus and species of a furry, bivalve–associated pontoniine shrimp is described from Palau. This is the second pontoniine shrimp known to be associated with bivalves burrowing into soft bottom, and the first record of a venus clam (Bivalvia, Veneridae) as host for caridean shrimps.